Rainfall-driven nutrient loading affects coastal phytoplankton in the southwestern Indian Ocean: a lagoon at Mauritius Island. Issue 2 (3rd April 2022) - Soondur, M; Boojhawon, R; Lowe, R; Kaullysing, D; Casareto, BE; Suzuki, Y; Bhagooli, R
Abstract : This study aimed to test the effects of rainfall-driven nutrient loading on the microphytoplankton dynamics in the shallow water at Trou aux Biches lagoon on the northwest coast of Mauritius. Changes in density, diversity and estimated productivity of microphytoplankton were monitored in three zones—coast, lagoon and reef—during two rainfall periods of 4 and 3 days' duration, respectively, in March–April 2017. The average nutrient loading from terrestrial runoff was 15.5% and the salinity decreased by 2.5%. Following the two rainfall events, a 3-fold increase in total microphytoplankton density (TMPD), with a dominance of diatoms, was noted within a week at the coast and lagoon, while it remained relatively unchanged at the reef. These changes in microphytoplankton densities were concomitant with adequate levels of silicate (>2 µM) and high nitrate:silicate ratios (2.84–6.93). During this study, the numbers of genera of diatoms, dinoflagellates and cyanobacteria observed were 28, 12 and 3, respectively. The Shannon–Wiener, equitability and evenness indices showed high diversity values for diatoms and cyanobacteria prior to the rainfall events and for dinoflagellates after the events. The chlorophyll a content, relative electron transport rate, and estimated productivity of microphytoplankton increased during and after the rainy periods. TMPD and chlorophyll a were correlated significantly and positively with nutrients, salinity and temperature. Toxic algal species such as the dinoflagellates Alexandrium, Dinophysis and Tripos were recorded, although not in bloom densities. These findings indicate that rainfall-driven nutrient loading led to an increase in microphytoplankton density and estimated productivity, and a change in its diversity.